Peer effect in the initial recognition of goodwill - Liping Xu; Yueqin Guan; Zhihong Fu; Xin Yu (China Journal of Accounting Research, 2020)
This study investigates the peer effect in the initial recognition of goodwill. We find that firms imitate their peers in the initial recognition of goodwill. The higher the tendency for imitation, the higher the proportion of goodwill recognized. Imitation behavior in the initial recognition of goodwill cannot be explained by information acquisition or rivalry motivations. Instead, we find evidence that managers' opportunistic motivations explain the peer effect in the initial recognition of goodwill and the overestimation of goodwill arising from imitation tendencies. Executive overconfidence weakens the peer effect but exacerbates the overestimation of goodwill caused by imitation tendencies. Finally, the higher the imitation tendency, the greater the probability and amount of goodwill impairment in the future. This further confirms that the peer effect leads to overestimation of goodwill. The findings of this study enrich the literature on goodwill and provide insightful empirical evidence for regulating goodwill accounting. The results show that the conservatism principle should be reinforced in the initial recognition of goodwill.
Keywords: 650; Initial Recognition of Goodwill; Peer Effect; Goodwill Impairment